Growth, yield and nutrient uptake by sesame as influenced by intercropping systems and sulphur levels under semi-arid region of Rajasthan - Shivran, A. C.; Yadav, R. K. (Annals of Agricultural Research, 2016)
An experiment was carried out at Jobner, Rajasthan during kharif season of 2011 to find out theeffect of intercropping system and sulphur level in sesame. The effect of intercropping systemsrevealed that planting of mothbean and sesame in 2:1 paired row ratio recorded significantly higherdry matter accumulation at 60 DAS and at harvest and N, P and S concentration in seed and stoverof sesame as compared to sole sesame. However, plant height at all the growth stages, dry matteraccumulation at 30 DAS and oil content in seed of sesame remained statistically same as sole crop.Highest seed yield (7.21 q/ha) and total uptake of N, P and S in sesame was recorded in sole cropwhich significantly higher than intercropping systems. However, significantly highest sesameequivalent yield (7.90 q/ha), land equivalent ratio (1.11) and net monetary returns (Rs 24150/ha)were registered with mothbean + sesame (2:1) intercropping system. The graded levels of sulphurup to 40 kg/ha significantly increased plant height and dry matter accumulation at different growthstages, N concentration in seed and stover, P concentration and oil content in seed and total uptakeof N and P, seed yield (4.46 q/ha), sesame equivalent yield (7.95 q/ha), LER (1.08) and net returns(Rs 24540/ha). However, significant improvement in P concentration in stover, S concentration inseed and stover and total S uptake were observed up to 60 kg S/ha. Thus application of 40 kg S/hain sesame intercropping system was found suitable considering input economy as it recorded 28.62and 8.20% higher seed yield and 42.12 and 10.93% higher net monetary returns over control andapplication of 20 kg S/ha, respectively.